2018
DOI: 10.1097/anc.0000000000000549
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Premature Infant Sleep/Wakefulness and Noise Levels in the Presence or Absence of “Quiet Time”

Abstract: Background: Peak sound levels during sleep can compromise the development of hospitalized infants. Quiet time is a strategy implemented in neonatal units to promote the sleeping of neonates by reducing noise levels, luminosity, and handling during particular periods of the day. Purpose: To determine the impact of quiet time on reducing sound levels and increasing total sleep time. Methods: This longitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 23 publications
1
34
0
1
Order By: Relevance
“…Quiet Time in the NICU Quiet time has been implemented in NICUs across the country as part of efforts to provide more developmentally appropriate care for hospitalized infants (AAP Committee on Fetus and Newborn & ACOG Committee on Obstetric Practice, 2007). Our findings are consistent with previous studies, suggesting that quiet time is associated with reduced noise (Casavant et al, 2017;Chawla et al, 2017;Laubach et al, 2014;Pugliesi et al, 2018;Wang et al, 2014). Although most of the previous researchers evaluating quiet time identified a reduction in noise levels (L eq ), we identified a decrease in the amount of time in which infants in the NICU were exposed to electronic noises.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Quiet Time in the NICU Quiet time has been implemented in NICUs across the country as part of efforts to provide more developmentally appropriate care for hospitalized infants (AAP Committee on Fetus and Newborn & ACOG Committee on Obstetric Practice, 2007). Our findings are consistent with previous studies, suggesting that quiet time is associated with reduced noise (Casavant et al, 2017;Chawla et al, 2017;Laubach et al, 2014;Pugliesi et al, 2018;Wang et al, 2014). Although most of the previous researchers evaluating quiet time identified a reduction in noise levels (L eq ), we identified a decrease in the amount of time in which infants in the NICU were exposed to electronic noises.…”
Section: Discussionsupporting
confidence: 92%
“…Current practice models designed to improve the environment tend to focus on minimizing noise stimulation through the renovation of NICU spaces to include private rooms; education for staff about the toxic effects of noise; and implementation of quiet time in which staff are encouraged to keep conversations quiet, respond to alarms quickly, and minimize procedures and patient handling (Rand & Lahav, 2014;Szymczak & Shellhaas, 2014). Implementation of a quiet time protocol in the NICU has led to significant reductions in noise levels (L eq ) during quiet time compared with nonquiet time (Chawla et al, 2017;Laubach et al, 2014;Pugliesi et al, 2018;Wang et al, 2014). In one study, researchers observed a 26% reduction in L eq during quiet time, which correlated with improved sleep in preterm infants (Pugliesi et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The uterus is an ideal environment for the fetus, where the anatomical, physiological, and neurophysiological structures of the fetus develop and mature. 23 Because their central nervous system is immature, premature infants are vulnerable to environmental stimuli and cannot coordinate autonomous responses to environmental and tactile stimuli. 24 Uterine walls can reduce the decibels (dB) of sound, and the fetus is exposed to approximately 28 dB in the uterus; however, in the NICU, the sounds are much louder, as high as 70 to 80 dB.…”
Section: Risk Factors For Hearing Loss In Premature Infantsmentioning
confidence: 99%
“…24 Uterine walls can reduce the decibels (dB) of sound, and the fetus is exposed to approximately 28 dB in the uterus; however, in the NICU, the sounds are much louder, as high as 70 to 80 dB. 23 The main sources of noise are human voices and device alarms and sounds, including incubators. Even simple things, such as the sound of running water, closing incubator doors, placing bottles, and the nasal continuous positive airway pressure (NCPAP) airflow will increase the decibel value of the NICU.…”
Section: Risk Factors For Hearing Loss In Premature Infantsmentioning
confidence: 99%